A descriptive morphological study on adult facial ageing in black South African males - Schmidlin, Estha J (My University, 2019)
Facial ageing research contributes to the knowledge spheres of plastic surgery, dermatology and craniofacial depiction. No South African specific facial ageing data are available. The aim of this study was therefore to assess aspects of facial ageing in a group of South African black males, using anterior and lateral facial photographs of 189 South African males aged 20 years and older. The sample included 30 individuals per decade, except for the 80+ age category that consisted of nine participants. Photos were recorded in a standardized manner and various metric and morphological features, related to increasing age, were assessed on each photograph. Non-metric facial changes were investigated using a facial scoring system based on existing literature. A more global approach to the face was also taken in construction of facial averages using Abrosoft FantaMorph Deluxe software. Socio-economic and demographic factors that may influence facial ageing were included in a lifestyle questionnaire. Overall, the results indicated some deviation from European-based literature on facial ageing. Mouth width increase, nasal elongation, nasal tip dropping, ear width increase and ear length increase did not occur with increasing age. Unique age changes, such as the lack of a lateral nose crease and the occurrence of a dimpled chin, were identified. Overall, wrinkle formation was delayed and cheek hollowing was advanced in this group relative to their European counterparts. A description of facial ageing in a South African male sample is provided by this study.
A Dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Medicine. Johannesburg, 2019